Analisa Rasio Efektivitas, Rasio Efisiensi dan Rasio Kemandirian Keuangan Daerah Terhadap Anggaran Pendapatan Dan Belanja Daerah (APBD) - Cut Delsie Hasrina (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2019)
Analysis of financial ratios to Regional Revenue and Expenditure Budget (APBD) is one of the parameters in measuring the performance of regional financial management. Financial performance analysis uses the calculation of the ratio of effectiveness, efficiency and independence of regional finances. This research aims to measure the financial performance of  Banda Aceh City Local Government during the fiscal year of 2014 to 2018. The research type is descriptive using the ratio analysis method. The results showed that the effectiveness ratio was categorized as effective against the APBD, and the efficiency ratio was categorized as less efficient towards the APBD. The independence ratio of regional financial management is still low.